Análise da influência do tronco e quadril em indivíduos com e sem discinese escapular - Pires, Elisa Doria (2017)
The scapula is a key component in the movements involving the upper limbs because, as it promotes a connection between the central segment of the body and upper distal segments. Based on that, the scapula is a link between the trunk and arm, and is part of the kinetic chain. As scapular dyskinesis can occur in the absence of shoulder symptoms, it is possible that alterations may also occur in other segments, such as trunk and hips in individuals without dyskinesis. Objective: The primary objective was to measure strength of the trunk flexors, trunk lateral flexors and hip extensors and abductors, and to compare the Y Balance Test (YBT) and Upper Quarter Y Balance Test (YBT-UQ) in indivuduals without and with scapular dyskinesis. The secondary purpose was to measure strength of lower trapezius, serratus anterior, and latissimus dorsi and endurance of the scapulothoracic muscles in the same individuals. Methods: Forty-four individuals without shoulder pain were divided in 2 groups: control group (26.00±4.10 years, 68.28±13.07 kg, 1.67±0.10 m) and scapular dyskinesis (23.68±4.20 years, 66.02±13.77 kg, 1.70±0.10 m). Scapular dyskinesis was assessed by clinical observation of the scapular motion during elevation of the arm in the sagittal and frontal planes, and was classified as “present” or “absent”. Present was considered when obvious dyskinesis was observed. A handheld dynamometer was used to measure the isometric muscle strength of the trunk flexors, trunk lateral flexors, hip extensors, hip abductors, lower trapezius and serratus anterior, and latissimus dorsi. The YBT and YBT-UQ were performed in anterior, posteromedial and posterolateral directions, and in medial, superolateral, and inferolateral, respectively. The individuals were positioned in prone on a treatment table with the arm positioned at 135° arm abduction to determine the endurance of the scapulothoracic muscles. The order of tests was randomized. For statistical analysis, Shapiro-Wilk test was used to check normality of the data. Independent t test and Mann-Witney test were used for comparison between groups. A p<0.05 was considered significant. Effect sizes between groups for all variables were calculated using the Cohen’s d coefficient. Results: No significant differences (p>0.05) were found between groups for all variables. However, Cohen’s d coefficient showed a moderate effect (d~0.40) for the trunk flexors and hip extensors, and endurance of the scapulothoracic muscles, whereas the scapular dyskinesis group showed less strength and endurance in relation to the control group. Conclusion: The results indicate that the trunk flexors, hip extensors muscles, and endurance of the scapulothoracic muscles seem to have influence in scapular dyskinesis in non-athletes without shoulder pain.